NNESTs’ Professional Identity in the Linguistically and Culturally Diverse Classrooms - Kim Hyunsook Song; Alla Gonzalez Del Castillo (International Journal of Educational Psychology, 2015)
This study examines NNESTs’ professional identities as classroom teachers by analyzing NNESTS’ perceptions of their strengths and challenges. The study contributes to NNESTs forming their professional identity by recognizing, developing, and contesting authoritative discourse. A basic qualitative research design is employed to analyze the interview data. Participants are five NNESTs who teach in American classrooms. Three focused themes are identified; linguistic competence, cross-cultural competence, and pedagogical competence. NNEST superiority fallacy is added as the fourth theme. Additionally, the study briefly compares strengths and challenges of U.S. versus foreign graduates. NNESTs’ strengths and challenges are reported in line with other NNEST researchers: dual-language acquisition and cross-cultural experience, grammar knowledge, linguistic theories, and coping strategies as strengths, poor command of English language, lack of sociocultural strategies, and lack of confidence as weaknesses. New findings include NNESTs’ confidence as effective teachers with accent, intellectual competence in theories, and stronger credentials. This study asserts that the NNESTs’ multilingual and multicultural backgrounds can become valuable assets with less linguistic prejudice, and the need for a policy that provides the benchmark to measure their credentials rather than depending on biased assumptions. Suggestions to shape NNESTs’ professional identity are provided